Value As The Core Tenet For Quality Media Education - Need, Challenges And Future: With Special Reference To Dev Sanskriti University's Value Based Education - Sukhnandan Singh (Dr. Chinmay Pandya, 2020)
Today looking at the all prevailing and wide role of media in the society, its lack of quality content, negative coverage and resulting negative impact on the society is a matter of great concern. Most of the journalists and mass communicators are the product of some Journalism and Mass communication or media schools/colleges/institutions. The state of media education in these institutions is a matter of grave concern. They are far away from the objective of giving products that can play their role as a force of positive change in the society. To forge journalists with a sense of professional commitment, social responsibility and a minimum sense of value sensitivity, is the need of the hour and also a big challenge to implement. How can the center of higher learning be the breeding ground for such products is a million dollar question? Researcher has firm opinion that values are the core requirement of quality media education. Education without value is like body without soul. There is need to revive the values. The present paper is a humble effort in this direction, based on personal observations, long concern with value education and the experiment on value based education going on at Dev sanskriti University, Haridwar, Uttarrakhand, India.